HUBUNGAN PERILAKU MEROKOK DENGAN PENGGUNAAN NAPZA JENIS AMPHETAMIN PADA MAHASISWA PERHOTELAN PERGURUAN TINGGI DI KOTA DENPASAR TAHUN 2019: THE RELATIONSHIP OF SMOKING BEHAVIOR WITH THE USE OF AMPHETAMIN TYPE OF DRUGS IN HIGHER EDUCATION HOSPITALITY STUDENTS IN DENPASAR 2019 - Idayani, Sri; Putri, Ni Luh Nova Dilisca Dwi (Stikes Wira Medika Bali, 2020)
One of the factors that influence drug abuse is smoking. The risk of drug abuse tends to increase in someone who has the habit of smoking and drinking alcohol. Some of the driugs are Narcotics, Psychotropic and other dangerous Addictive Materials. One of the drugs is amphetamine. Amphetamine can be white, yellow or cocoa powder, or small crystalline white powder and can also be in the form of pharmaceutical preparations (tablets). This study aims to determine the relationship between smoking behavior with the use of drug type amphetamines in the urine of hospitality students at Denpasar City University in 2019. Smoking behavior was analyzed from interviews using questionnaires and the amphetamine content of urine was tested using the rapid diagnostic test method. The number of urine samples analyzed was 27 university hospitality students in the city of Denpasar. The results showed that the Chi-Square statistical test obtained p-value of no statistical data generated due to the use of constant type of amphetamine NAPZA. This means that there is no relationship between smoking behavior with the use of drug type amphetamines in the urine of hospitality students at Denpasar City University in 2019.